DEBTOR’S DEFAULT AND BRI CREDIT GUARANTEE AUCTION PROCEDURE - Saifudin Wahid; Appe Hutauruk; Hotman Sinambela; Fendi Maruba Parlindungan Hutahaean (JILPR Journal Indonesia Law and Policy Review, 2026)
The reality of the credit relationship practice between CV. SAMIJAYA and BRI which resulted in installment arrears, a collateral auction plan through KPKNL with a limit value that was considered very low, as well as the decision of the Central Jakarta District Court Number 397/Pdt.G/2025/PN Jkt.Pst which stated that the Plaintiff’s lawsuit was dismissed so that the main case regarding the debtor’s default and the collateral auction procedure was never examined substantially by the judge. The provisions of the Civil Code, especially Article 1234 concerning performance and Article 1338 concerning the principle of freedom of contract, as well as Article 1365 and Article 1367 concerning unlawful acts and responsibility for losses. In addition, Law Number 4 of 1996 concerning Mortgage Rights on Land and Objects Related to Land, especially Article 6, Article 20, and Article 26 concerning executorial title and parate execution, execution provisions in HIR, especially Article 124, Article 200, and Article 224; Law Number 8 of 1999 concerning Consumer Protection (Article 4 letter c concerning the right to information), and Law Number 10 of 1998 concerning Banking, which together require that the implementation of parate execution rights and credit guarantee auction procedures by banks be carried out transparently, proportionally, and in line with the principles of legal certainty and protection for debtors, especially small and medium business actors. The purpose of this study is to analyze the definition and classification of debtor default in BRI credit agreements based on Decision No. 397/Pdt.G/2025/PN Jkt.Pst and to analyze the BRI credit guarantee auction procedure and its implications for debtor protection based on Decision No. 397/Pdt.G/2025/PN Jkt.Pst. This study uses a normative juridical method with a statutory approach and a case approach, based on secondary data in the form of laws and regulations, court decisions, and doctrines. The results of the study indicate that the debtor CV. SAMIJAYA is normatively in a state of default due to prolonged payment arrears so that it cannot be qualified as force majeure; Thus, BRI as the holder of the mortgage has a legal basis to carry out the execution of the guarantee as long as the procedure is in accordance with the provisions, the credit guarantee auction procedure through the KPKNL which is based on the mortgage certificate and the Minister of Finance Regulation Number 122 of 2023 without the involvement of the fiat of the Head of the District Court and by setting a limit value that is far below the market price, it creates problems with the hierarchy of norms and has the potential to cause excessive losses to debtors, so that the practice of parate execution needs to be aligned with the HIR/RBg, the principle of legal certainty, and the principle of consumer protection for financial services.